Comparative effects of oral nutritional supplementation vs. nutritional education on appetite and weight in older adults with anorexia of aging: a 12-week non-randomized controlled trial - Feng, Gaojie; Liu, Chen; Sun, Xiaohong; Liu, Xiaohong; Lu, Fei; Li, Yuanyuan; Zhou, Yaru (Frontiers in Nutrition, 2025)
BackgroundWith global aging, diet education and oral nutritional supplements (ONS) are recognized for improving nutrition and appetite in older adults, yet evidence on anorexia of aging (AA) mechanisms and interventions remains limited in China. This study aimed to evaluate diet education and ONS efficacy for AA in Chinese community-dwelling older adults.MethodsIn an open-label, non-randomized controlled trial, 64 eligible participants were allocated to an ONS group (supplementation) or a diet education group. The Simplified Nutritional Appetite Questionnaire (SNAQ) assessed AA, with follow-ups at weeks 2, 4, 8, and 12. Primary outcomes were SNAQ improvements; secondary outcomes included weight, grip strength, nutritional status (BMI, MNA-SF), cognition (MMSE), mobility (SPPB), mental health (GDS15), and quality of life (EQ-5D).ResultsYounger, non-solo-living, and malnourished participants preferred ONS intervention (p < 0.05). Both groups showed increased SNAQ scores versus baseline (counseling: weeks 4/8/12; ONS: weeks 2/4/8/12), with ONS achieving significantly greater improvement at week 2 (p < 0.05). Weight remained unchanged in both groups (p > 0.05). Diet education increased grip strength at week 12 (p < 0.05), while no significant improvements occurred in BMI, cognition, mobility, or quality of life.ConclusionBoth ONS and diet education alleviated AA over 12 weeks, but ONS demonstrated earlier efficacy (significant SNAQ improvement by week 2). However, ONS did not enhance weight, physical function, or cognitive outcomes.Trial registrationApproved by Peking Union Medical College Hospital Ethics Committee (I-23PJ661), registered at Chinese Clinical Trial Registry (MR-11-23-023104).